Perbaikan Teknik Relining Tanur Induksi Untuk Mencegah Terbentuknya Rongga Lining dan Penghematan Biaya Proses Peleburan - Tridaryanto, Anto; Sutoyo, Sutoyo; Hidayat, Mansur (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
The lining is coil’s protector componen and metal liquid reservoir, the lining is required to own endurance towards chemical reaction and high temperature emitted by the smelting process. The lining commonly problem on the lining damage (cavity) after the sintering process. This damage cause the smelting process force-stopped, due to endangering the induction furnace operator and the surrounding. According to the analysis result, the lining damage occured because of the improper pulverization and sintering process with the casting term. The uncontinued comprssion process and the improper sintering with the used fireproof material, cause the lining can not maximally functioned. The upcoming refinement will apply proper compression process according to metal casting theories and economically anallyzed.